Preparation method of cable-shaped structure SiO2-coated SiC composite wave-absorbing material
By using waste biomass and silicon powder for high-temperature chemical vapor phase reaction, cable-like SiO2@SiC nanowires were prepared, which solved the complex and cost-effective preparation of SiO2@SiC nanowires in the prior art, and achieved efficient wave absorption Performance and high-value utilization of biomass.
Patent Information
- Application Number
- CN202411422308.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The existing technology lacks a method for preparing SiO2@SiC nanowires through chemical vapor phase reaction using industrial silicon and biomass carbon as raw materials. The traditional process is complex and costly, making it difficult to achieve high-efficiency absorbing performance and low cost of porous silicon carbide materials. Simple preparation.
Use natural waste biomass such as coffee shells, peanut shells, rice shells, etc. as carbon sources, and silicon powder and silica powder are used as silicon sources. Carbon-heat reduction is carried out in the crucible through high-temperature chemical vapor phase reaction to prepare SiO2 with a cable-like structure. @SiC composite absorbing material, calcium carbonate powder is used to generate CO2 gas to control the reaction, forming high-quality SiO2@SiC nanowires.
The SiO2@SiC nanowires with high-efficiency absorption performance were prepared under low-cost and simple process flow. The optimal reflection loss reached -50.40dB and the maximum effective absorption bandwidth was 4.52GHz, providing a high-value recycling and utilization method for waste biomass. .
Smart Images

Figure CN119240703A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicon carbide absorbing materials, and in particular relates to a method for preparing a SiO2@SiC composite absorbing material with a cable-like structure. Background Art
[0002] Absorbing material is a material that can absorb or weaken incident electromagnetic waves. It can convert the electromagnetic wave energy absorbed from the outside into heat energy and dissipate it. It is a vital material in fields such as radar monitoring.
[0003] The one-dimensional structure of silicon carbide nanowires, due to its unique nanoscale fiber structure, also has the characteristics of wide band gap, high dielectric loss, high specific surface area and corrosion resistance. It is often used as a reinforcing material to make up for the defects in composite materials. Therefore, it is considered to be a potential material for preparing high-performance electromagnetic wave absorbing materials.
[0004] Traditionally, silicon carbide nanowires are made from silicon carbide powder through gel casting, foaming and freezing. These processes are complex and require additional additions to complete. Therefore, the construction of porous silicon carbide materials with high-efficiency wave absorption performance through low-carbon, simple and economical methods has aroused great interest. Patent 1 "CN 118387866A" uses natural microcrystalline graphite as a carbon source to prepare SiC / C composite absorbers at 1350-1600℃, with an impedance matching coefficient |Zin / Z0|≈1, reflection loss ≤-20dB, and effective absorption bandwidth ≥2GHz. Patent 2 "CN 115504799A" uses calcium aluminate-wrapped carbon nanofiber cement as a binder, granular silicon carbide, activated alumina, silica ash and metallic silicon as raw materials, and prepares C / SiC absorbers through stirring, mixing, vibration molding and sintering processes. Patent 3 "CN202410624750.X" A silicon carbide crucible for aluminum alloy smelting and its preparation method, which relates to "A method for preparing a silicon carbide crucible for aluminum alloy smelting, characterized in that the specific steps of the preparation method are: the first step, 20-30wt% of silicon carbide particles A with a particle size of 0.5-1.0mm, 5-15wt% of silicon carbide particles B with a particle size of 0.1-0.5mm, 30-40wt% of silicon carbide fine powder A, 20-30wt% of silicon carbide fine powder B and 3-7wt% of xylitol are mixed to obtain a mixture A; the mixture A is placed in a silica sol, and the vacuum degree is - The invention relates to a method for preparing SiO2@SiC nanowires by chemical vapor reaction using industrial silicon and biochar as raw materials. The method comprises the steps of: distilling the mixture B under the conditions of 0.08 to -0.10 MPa for 20 to 40 minutes to obtain a mixture B; drying the mixture B at 90 to 110°C for 8 to 10 hours, and heat treating the mixture B at 400 to 600°C for 2 to 4 hours to obtain silicon dioxide-coated silicon carbide; the silicon carbide particles A, the silicon carbide particles B, the silicon carbide fine powder A and the silicon carbide fine powder B have the same chemical composition: the SiC content is greater than 97.0wt%, and the FeO content is less than 0.5wt%; "It can be seen that there are few reports in the prior art on the preparation of SiO2@SiC nanowires by chemical vapor reaction using industrial silicon and biochar as raw materials. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention proposes for the first time a method for preparing a SiO2@SiC composite absorbing material with a cable-like structure. The carbon source in the present invention is waste biomass in nature, such as coffee shells, peanut shells, rice husks, tobacco straws, cotton straws, etc. Most of these biomass are by-products of agricultural and forestry products, and most of these materials are discarded as waste. These waste biomass raw materials not only have high reactivity, but also have a highly porous structure. Fluffy and porous biochar can be obtained by direct carbonization. The large amount of alkali metals contained in these biomass itself make them have good reactivity in the carbon thermal reduction process. Therefore, the waste biomass is very suitable as a carbon source for generating silicon carbide nanowires. The silicon source is a mixed powder of silicon powder and silicon dioxide powder. A suitable carbon source and a silicon source are placed in a crucible, and SiO2@SiC nanowires with a cable-like structure are obtained by chemical vapor reaction at high temperature.
[0006] The present invention provides a method for preparing a cable-like structured SiO2@SiC composite absorbing material, and the specific steps are as follows:
[0007] (1) Carbon source pretreatment: Grind the clean biomass into powder to obtain pretreated material;
[0008] (2) Carbonization: The pretreated material obtained in step (1) is placed in a mold to be formed, and then placed in a furnace with a protective gas to be carbonized to obtain fluffy and porous biochar;
[0009] (3) Silicon source pretreatment: Silicon powder and silicon dioxide are fully mixed by ball milling to obtain a mixed silicon source containing silicon and silicon dioxide; the mass ratio of silicon powder to silicon dioxide is 1-2:2-1;
[0010] (4) High-temperature carbon thermal reduction: a layer of calcium carbonate powder is laid on the bottom of the crucible, and then the mixed silicon source obtained in step (3) is evenly spread on the surface of the CaCO3 powder, and then a corundum ring is placed as a support, and the fluffy porous biochar obtained in step (2) is placed on the upper end of the corundum ring; first, a protective gas is introduced, and then the temperature is raised to the reaction temperature, the reaction temperature is 1200-1600°C, and the reaction time is greater than 2 hours;
[0011] (5) Carbon removal and controlled oxidation: The product obtained in step (4) is directly placed in a muffle furnace for heating to remove residual carbon and controllably oxidize to obtain SiO2@SiC nanowires; the temperature for carbon removal and controlled oxidation is 890-910°C and the time is greater than or equal to 100 min.
[0012] The invention discloses a method for preparing a SiO2@SiC composite wave absorbing material with a cable-like structure, wherein the biomass is selected from at least one of coffee shells, peanut shells, rice husks, tobacco straws and cotton straws. After being ground into powder, the particle size thereof is 50-100 meshes. When applied in industry, the target particle size powder can be obtained by vibration milling.
[0013] Preferably, the present invention provides a method for preparing a SiO2@SiC composite absorbing material with a cable-like structure, wherein the powdered biomass is placed in a mold and vacuum dried to form the biomass; the vacuum drying temperature is -50°C to -40°C, and the drying time is 12 to 24 hours. Of course, other drying methods may also be applicable to the present invention. The reason why freeze drying is preferred in the present invention is that freeze drying allows the biomass to maintain its original void structure, and a more fluffy and porous biochar can be obtained during the carbonization process.
[0014] The present invention discloses a method for preparing a SiO2@SiC composite wave absorbing material with a cable-like structure. The pre-material obtained in step (1) is placed in a tubular furnace filled with argon gas for carbonization to obtain fluffy and porous biochar.
[0015] Preferably, the present invention provides a method for preparing a cable-like structured SiO2@SiC composite absorbing material.
[0016] During carbonization, the argon gas flow rate is 8-25 ml / min, the carbonization temperature is 500-800°C, and the time is greater than or equal to 100 min. In practical applications, the carbonization time can be appropriately extended according to the amount of material and the degree of carbonization.
[0017] Preferably, in the method for preparing a cable-like structured SiO2@SiC composite absorbing material of the present invention, in step (3), the purity of the silicon and silicon dioxide powders used is >99wt%, and the mesh size is -100 mesh.
[0018] Preferably, in the method for preparing a cable-like structure SiO2@SiC composite absorbing material of the present invention, in step (3), the silicon powder and silicon dioxide used are prepared in a mass ratio of 1:2, and the optimal reflection loss (RL min ) is less than -50dB, the maximum effective absorption bandwidth (EAB max ) is a high-quality product with a frequency greater than 4.5GHz.
[0019] During the high-temperature carbon thermal reduction of the present invention, the crucible is almost composed of an atmosphere system of CO / CO2+SiOx, which is a little different from the atmosphere outside the crucible, where there is a protective gas. The reason why the protective gas outside the crucible is controlled to move at an extremely low flow rate is to prevent the reaction gas in the crucible from being excessively fluctuated by the atmosphere, thereby causing abnormal reactions. At the same time, the air pressure inside and outside the crucible is basically the same. The crucible cover cooperates with the low-flow rate protective gas outside the crucible to ensure that the reaction in the crucible is as little affected by the outside world as possible. Therefore, as a preferred embodiment, the present invention also needs to control the flow rate of the protective gas (such as argon) outside the crucible to 8-20 ml / min.
[0020] Preferably, in the preparation method of a cable-like structure SiO2@SiC composite absorbing material of the present invention, in step (4), the reaction temperature is 1400-1600°C, more preferably 1580-1600°C. A higher reaction temperature combined with the mixing of silicon powder and silicon dioxide in the silicon source in a mass ratio of 1:2 and other conditions can obtain a product with extremely excellent performance. SiC is an electromagnetic wave absorbing material, and SiO2 is a transparent material for electromagnetic waves. When electromagnetic waves are incident on the SiO2@SiC material, the outermost SiO2 coating can prevent the electromagnetic waves from being directly reflected, but first penetrates the SiO2 outer layer, and then passes through the SiO2 / SiC heterogeneous layer to reach the inside of the SiC core, so that the electromagnetic energy is converted into heat energy for dissipation. The SiO2 coating allows the incident electromagnetic wave to reach the SiC core more smoothly. After SiC absorbs part of the energy, part of the electromagnetic wave energy will be reflected. The accumulated charge and interface polarization of the SiO2 / SiC heterogeneous layer will cause the reflected electromagnetic wave to be reflected back to the SiC core again. Therefore, the multi-layer and multi-site reflection and interface polarization brought by SiO2 will improve the material's wave absorption and energy absorption. At the same time, the reaction temperature of the present invention is increased. According to the reaction mechanism, when the silicon carbide fiber is generated, there are trace amounts of silicon oxides inside. These trace amounts of silicon oxides are beneficial to improving the electromagnetic performance of the product. Therefore, in practical applications, in order to pursue lower reflection losses and wider absorption bandwidths, a reaction temperature of 1580 to 1600°C can be used.
[0021] Preferably, in the method for preparing a cable-like structured SiO2@SiC composite absorbing material of the present invention, in step (4), after the reaction temperature is kept warm, the temperature is lowered at a rate of 4-6°C / min.
[0022] Preferably, in the method for preparing a SiO2@SiC composite wave absorbing material with a cable-like structure of the present invention, in step (4), the mass ratio of calcium carbonate to silicon source is 1:1.1-1.5, preferably 1:1.2-1.5. The purpose of using calcium carbonate in the present invention is to make CO2 the dominant gas in the system, inhibit reaction (4), and make the reaction proceed to reaction (5). The purpose of controlling the mass ratio of calcium carbonate to silicon source to 1:1.2-1.5 is to control the relative content of CO2 and SiO gas in the system, and the CaO generated during the reaction will consume part of the silicon source. At the same time, it is also found that compared with the system without adding calcium carbonate, the diameter distribution of the product obtained by the present invention is narrower.
[0023] In step (4), the mass ratio of the fluffy porous biochar to the silicon source is preferably fluffy porous biochar: silicon source = 3.0-6.5:7.5.
[0024] Preferably, in the preparation method of a SiO2@SiC composite absorbing material with a cable-like structure of the present invention, the product obtained in step (4) is directly placed in a muffle furnace for heating, and heated to 890-910°C at a heating rate of 8-12°C / min, and then kept warm for 110-130min to remove residual carbon and controllably oxidize to obtain SiO2@SiC nanowires. If the temperature is too low, too little silicon dioxide will be generated in a short time, or even no continuous silicon oxide layer will appear. In the most extreme case, only the outer layer of the silicon carbide fiber does not contain silicon oxide. If the temperature is too high, the silicon dioxide coating will be incomplete or the coating quality will be too poor (mainly uneven).
[0025] In (4),
[0026] As the reaction temperature gradually increases, the CaCO3 powder at the bottom layer will be decomposed and release a large amount of CO2 gas after being heated. CO2 gas and carbon source will generate CO gas at high temperature; the mixed silicon source composed of Si and SiO2 will undergo a disproportionation reaction at high temperature to generate a large amount of SiO gas. In a closed environment, a SiC substrate will first be formed through reaction (4) at high temperature. In the cooling stage, in an environment where CO2 gas is the dominant gas, reaction (5) is suppressed, and both CO gas and SiO gas will proceed toward reaction (6). When the temperature starts to drop in the later stage of the reaction, since the melting point of silicon oxide is much lower than that of SiC, starting to cool down at a higher temperature and controlling the rate will form a relatively uniform silicon oxide film on the outer layer of the obtained SiC. The specific reaction mechanism is as follows:
[0027] CaCO3(s)=CaO(s)+CO2(g)#(1)
[0028] SiO2(s)+Si(s)=2SiO(g)#(2)
[0029] CO2(g)+C(s)=2CO(g)#(3)
[0030] SiO(g)+2C(s)=SiC(s)+CO(g)#(4)
[0031] SiO(g)+3CO(g)=SiC(s)+2CO2(g)#(5)
[0032] 3SiO(g)+CO(g)=SiC(s)+2SiO2(s)#(6);
[0033] The outer layer of the SiO2@SiC nanowire obtained by the present invention is silicon dioxide, and the inner layer is silicon carbide; or the outer layer of the SiO2@SiC nanowire obtained by the present invention is silicon dioxide, and the inner layer is silicon carbide and a trace amount of silicon oxide.
[0034] The beneficial effects of the present invention are:
[0035] (1) The present invention uses waste biomass as raw material, which has low raw material cost and simple and fast process flow. Fluffy and porous biochar can be obtained after vacuum drying, providing a high-value recycling method for waste biomass.
[0036] (2) The large amount of alkali metals contained in the biomass of the present invention makes it have good reaction activity in the carbon thermal reduction process.
[0037] (3) In the present invention, more CO2 gas is generated by adding CaCO3 powder, so that the subsequent reaction is more complete.
[0038] (4) The present invention uses a simple chemical vapor reaction method to prepare SiO2@SiC nanowires with high microwave absorption performance and the best reflection loss (RL min ) is -50.40dB, the maximum effective absorption bandwidth (EAB max ) is 4.52GHz. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Attached Figure 1 This is a process flow chart for preparing SiO2@SiC nanowires in Example 1;
[0040] Attached Figure 2 This is a schematic diagram of a specific reaction device in Example 1;
[0041] Attached Figure 3 This is the microscopic morphology prepared using coffee shell as the carbon source in Example 1;
[0042] Attached Figure 4 This is a transmission electron micrograph of the product prepared using coffee shell as a carbon source in Example 1;
[0043] Attached Figure 5 This is an energy spectrum characterization diagram of the product prepared using coffee shell as a carbon source in Example 1;
[0044] Attached Figure 6 This is a test of the microwave absorption performance of the sample prepared using coffee shells as the carbon source in Example 1;
[0045] Attached Figure 7 This is the microscopic morphology prepared using coffee shell as the carbon source in Comparative Example 1;
[0046] Attached Figure 8 This is an energy spectrum characterization diagram of the product prepared using coffee shell as the carbon source in Comparative Example 1.
[0047] from Figure 1 The basic process flow of the present invention can be seen.
[0048] from Figure 2 It can be seen that the basic composition and structure of the reaction device used in the present invention.
[0049] from Figure 3 It can be seen that a large number of nanowires are interwoven to form nanogaps.
[0050] from Figure 4 It can be seen that the nanowire has a diameter of 28nm and has a 2nm thick shell.
[0051] from Figure 5 It can be seen that the color distribution of O and Si overlaps, the distribution color is lighter, and there is a layer of amorphous SiO2.
[0052] from Figure 6 It can be seen that the optimal dielectric loss is -50.40dB, which is equivalent to being able to dissipate 99.999% of the electromagnetic wave energy.
[0053] from Figure 7 It can be seen that the nanowires are intertwined and entangled.
[0054] from Figure 8 It can be seen that the O content is very small and the color does not overlap with Si. DETAILED DESCRIPTION
[0055] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0056] Example 1: A method for preparing a SiO2@SiC composite absorbing material with a cable-like structure, the specific steps are as follows:
[0057] (1) grinding coffee husks into powder and placing them in a circular mold, and then vacuum drying the powder at -45°C;
[0058] (2) placing the coffee husk (10 g) vacuum-dried in step (1) into a horizontal tube furnace filled with argon gas at a flow rate of 10 ml / min, a carbonization temperature of 600° C., a heating rate of 10° C. / min, and a holding time of 2 h to obtain 3.85 g of coffee husk biochar;
[0059] (3) grinding silicon powder and silicon dioxide, both with a purity of more than 99 wt%, in a ball mill at a mass ratio of 1:2 for 5 h to obtain a mixed silicon source composed of Si and SiO2;
[0060] (4) 5 g of CaCO3 powder was placed at the bottom of the crucible to generate CO2 gas, and then the carbon source (3.85 g) and silicon source (7.5 g) obtained in step (2) and step (3) were placed in a corundum crucible. The crucible was covered with a lid and placed in a muffle furnace filled with argon for reaction. The argon flow rate was 10 ml / min, the maximum reaction temperature was 1600°C, the heating rate was 10°C / min, the holding time was 5 h, the cooling rate was 5°C / min, and 4.13 g of product was obtained after cooling to room temperature;
[0061] (5) The product obtained in step (4) was directly placed in a muffle furnace, heated to 900°C at a heating rate of 10°C / min, kept at this temperature for 2 h, and cooled to obtain 3.15 g of SiO2@SiC.
[0062] (6) The product obtained in step (5) is subjected to a wave absorption performance test, and the optimal reflection loss (RL min ) is -50.40dB, the maximum effective absorption bandwidth (EAB max ) is 4.52GHz. (Its diameter is distributed between 28-63nm)
[0063] Example 2: A method for preparing a SiO2@SiC composite absorbing material with a cable-like structure, the specific steps are as follows:
[0064] (1) grinding coffee husks into powder and placing them in a circular mold, and then vacuum drying the powder at -40°C;
[0065] (2) placing the coffee husk (10 g) vacuum-dried in step (1) into a horizontal tube furnace filled with argon gas at a flow rate of 10 ml / min, a carbonization temperature of 500° C., a heating rate of 10° C. / min, and a holding time of 2 h to obtain 6.24 g of coffee husk biochar;
[0066] (3) grinding silicon powder and silicon dioxide, both with a purity of more than 99%, in a ball mill at a mass ratio of 1:1.5 for 5 hours to obtain a mixed silicon source composed of Si and SiO2;
[0067] (4) 5 g of CaCO3 powder was placed at the bottom of the crucible to generate CO2 gas, and then the carbon source (6.24 g) and silicon source (7.5 g) obtained in step (2) and step (3) were placed in a corundum crucible. The crucible was covered with a lid and placed in a muffle furnace filled with argon for reaction. The argon flow rate was 10 ml / min, the maximum reaction temperature was 1500°C, the heating rate was 10°C / min, the holding time was 5 h, the cooling rate was 5°C / min, and 6.53 g of product was obtained after cooling to room temperature;
[0068] (5) The product obtained in step (4) was directly placed in a muffle furnace, heated to 900°C at a heating rate of 10°C / min, kept at this temperature for 2 hours, and cooled to obtain 1.94g of SiO2@SiC (whose diameter distribution ranged from 26 to 59nm).
[0069] (6) The product obtained in step (5) is subjected to a wave absorption performance test, and the optimal reflection loss (RL min ) is -12.18dB, the maximum effective absorption bandwidth (EAB max ) is 3.32GHz.
[0070] Example 3: A method for preparing a SiO2@SiC composite absorbing material with a cable-like structure, the specific steps are as follows:
[0071] (1) grinding coffee husks into powder and placing them in a circular mold, and then vacuum drying the powder at -50°C;
[0072] (2) placing the coffee husk (10 g) vacuum-dried in step (1) into a horizontal tube furnace filled with argon gas at a flow rate of 10 ml / min, a carbonization temperature of 700° C., a heating rate of 10° C. / min, and a holding time of 2 h to obtain 3.57 g of coffee husk biochar;
[0073] (3) grinding silicon powder and silicon dioxide, both with a purity of more than 99%, in a ball mill at a mass ratio of 1.5:1 for 5 hours to obtain a mixed silicon source composed of Si and SiO2;
[0074] (4) 5 g of CaCO3 powder was placed at the bottom of the crucible to generate CO2 gas, and then the carbon source (3.57 g) and silicon source (7.5 g) obtained in step (2) and step (3) were placed in a corundum crucible. The crucible was covered with a lid and placed in a muffle furnace filled with argon for reaction. The argon flow rate was 10 ml / min, the maximum reaction temperature was 1400°C, the heating rate was 10°C / min, the holding time was 5 h, the cooling rate was 5°C / min, and 4.58 g of product was obtained after cooling to room temperature;
[0075] (5) The product obtained in step (4) was directly placed in a muffle furnace, heated to 900°C at a heating rate of 10°C / min, kept at this temperature for 2 hours, and cooled to obtain 1.37g of SiO2@SiC (whose diameter distribution ranged from 25 to 53nm).
[0076] (6) The product obtained in step (5) is subjected to a wave absorption performance test, and the optimal reflection loss (RL min ) is -6.42dB. Example 4: A method for preparing a SiO2@SiC composite absorbing material with a cable-like structure, the specific steps are as follows:
[0077] (1) grinding coffee husks into powder and placing them in a circular mold, and then vacuum drying the powder at -45°C;
[0078] (2) placing the coffee husk (10 g) vacuum-dried in step (1) into a horizontal tube furnace filled with argon gas at a flow rate of 10 ml / min, a carbonization temperature of 800° C., a heating rate of 10° C. / min, and a holding time of 2 h to obtain 3.49 g of coffee husk biochar;
[0079] (3) grinding silicon powder and silicon dioxide, both with a purity of more than 99%, in a ball mill at a mass ratio of 2:1 for 5 hours to obtain a mixed silicon source composed of Si and SiO2;
[0080] (4) 5 g of CaCO3 powder was placed at the bottom of the crucible to generate CO2 gas, and then the carbon source (3.49 g) and silicon source (7.5 g) obtained in step (2) and step (3) were placed in a corundum crucible. The crucible was covered with a lid and placed in a muffle furnace filled with argon for reaction. The argon flow rate was 10 ml / min, the maximum reaction temperature was 1300°C, the heating rate was 10°C / min, the holding time was 5 h, the cooling rate was 5°C / min, and 3.82 g of product was obtained after cooling to room temperature;
[0081] (5) The product obtained in step (4) was directly placed in a muffle furnace, heated to 900°C at a heating rate of 10°C / min, kept at this temperature for 2 hours, and cooled to obtain 0.43g of SiO2@SiC (whose diameter distribution ranged from 26 to 49nm).
[0082] (6) The product obtained in step (5) is subjected to a wave absorption performance test, and the optimal reflection loss (RL min ) is -4.80dB. Example 5: A method for preparing a SiO2@SiC composite absorbing material with a cable-like structure, the specific steps are as follows:
[0083] (1) grinding tobacco straw into powder and placing it in a circular mold, and then vacuum drying the powder at -50°C;
[0084] (2) placing the tobacco straw (10 g) vacuum-dried in step (1) into a horizontal tubular furnace filled with argon gas at a flow rate of 10 ml / min, a carbonization temperature of 800° C., a heating rate of 10° C. / min, and a holding time of 2 h to obtain 3.35 g of tobacco straw biochar;
[0085] (3) grinding silicon powder and silicon dioxide, both with a purity of more than 99%, in a ball mill at a mass ratio of 1:2 for 5 hours to obtain a mixed silicon source composed of Si and SiO2;
[0086] (4) 5 g of CaCO3 powder was placed at the bottom of the crucible to generate CO2 gas, and then the carbon source (3.35 g) and silicon source (7.5 g) obtained in step (2) and step (3) were placed in a corundum crucible. The crucible was covered with a lid and placed in a muffle furnace filled with argon for reaction. The argon flow rate was 10 ml / min, the maximum reaction temperature was 1600°C, the heating rate was 10°C / min, the holding time was 5 h, the cooling rate was 5°C / min, and 5.22 g of product was obtained after cooling to room temperature;
[0087] (5) The product obtained in step (4) was directly placed in a muffle furnace, heated to 900°C at a heating rate of 10°C / min, kept at this temperature for 2 hours, and cooled to obtain 2.71g of SiO2@SiC (with a diameter distribution of 57-90nm).
[0088] (6) The product obtained in step (5) is subjected to a wave absorption performance test, and the optimal reflection loss (RL min ) is -43.68dB, the maximum effective absorption bandwidth (EAB max ) is 2.84GHz.
[0089] Example 6: A method for preparing a SiO2@SiC composite absorbing material with a cable-like structure, the specific steps are as follows:
[0090] (1) grinding tobacco straw into powder and placing it in a circular mold, and then vacuum drying the powder at -40°C;
[0091] (2) placing the tobacco straw (10 g) vacuum-dried in step (1) into a horizontal tubular furnace filled with argon gas at a flow rate of 10 ml / min, a carbonization temperature of 500° C., a heating rate of 10° C. / min, and a holding time of 2 h to obtain 5.78 g of tobacco straw biochar;
[0092] (3) grinding silicon powder and silicon dioxide, both with a purity of more than 99%, in a ball mill at a mass ratio of 2:1 for 5 hours to obtain a mixed silicon source composed of Si and SiO2;
[0093] (4) 5 g of CaCO3 powder was placed at the bottom of the crucible to generate CO2 gas, and then the carbon source (5.78 g) and silicon source (7.5 g) obtained in step (2) and step (3) were placed in a corundum crucible. The crucible was covered with a lid and placed in a muffle furnace filled with argon for reaction. The argon flow rate was 10 ml / min, the maximum reaction temperature was 1300°C, the heating rate was 10°C / min, the holding time was 5 h, the cooling rate was 5°C / min, and 6.89 g of product was obtained after cooling to room temperature;
[0094] (5) The product obtained in step (4) was directly placed in a muffle furnace, heated to 900°C at a heating rate of 10°C / min, kept at this temperature for 2 hours, and cooled to obtain 0.62g of SiO2@SiC (whose diameter distribution ranged from 47 to 76nm).
[0095] (6) The product obtained in step (5) is subjected to a wave absorption performance test, and the optimal reflection loss (RL min ) is -5.78dB. Example 7: A method for preparing a SiO2@SiC composite absorbing material with a cable-like structure, the specific steps are as follows:
[0096] (1) grinding tobacco straw into powder and placing it in a circular mold, and then vacuum drying the powder at -40°C;
[0097] (2) placing the tobacco straw (10 g) vacuum-dried in step (1) into a horizontal tubular furnace filled with argon gas at a flow rate of 10 ml / min, a carbonization temperature of 600° C., a heating rate of 10° C. / min, and a holding time of 2 h to obtain 4.07 g of tobacco straw biochar;
[0098] (3) grinding silicon powder and silicon dioxide, both with a purity of more than 99%, in a ball mill at a mass ratio of 1:1.5 for 5 hours to obtain a mixed silicon source composed of Si and SiO2;
[0099] (4) 5 g of CaCO3 powder was placed at the bottom of the crucible to generate CO2 gas, and then the carbon source (4.07 g) and silicon source (7.5 g) obtained in step (2) and step (3) were placed in a corundum crucible. The crucible was covered with a lid and placed in a muffle furnace filled with argon for reaction. The argon flow rate was 10 ml / min, the maximum reaction temperature was 1400°C, the heating rate was 10°C / min, the holding time was 5 h, the cooling rate was 5°C / min, and 5.28 g of product was obtained after cooling to room temperature;
[0100] (5) The product obtained in step (4) was directly placed in a muffle furnace, heated to 900°C at a heating rate of 10°C / min, kept at this temperature for 2 hours, and cooled to obtain 1.23g of SiO2@SiC (whose diameter distribution ranged from 54 to 87nm).
[0101] (6) The product obtained in step (5) is subjected to a wave absorption performance test, and the optimal reflection loss (RL min ) is -7.56dB. Example 8: A method for preparing a SiO2@SiC composite absorbing material with a cable-like structure, the specific steps are as follows:
[0102] (1) grinding tobacco straw into powder and placing it in a circular mold, and then vacuum drying the powder at -45°C to form a mold;
[0103] (2) placing the tobacco straw (10 g) vacuum-dried in step (1) into a horizontal tubular furnace filled with argon gas at a flow rate of 10 ml / min, a carbonization temperature of 700° C., a heating rate of 10° C. / min, and a holding time of 2 h to obtain 3.67 g of tobacco straw biochar;
[0104] (3) grinding silicon powder and silicon dioxide, both with a purity of more than 99%, in a ball mill at a mass ratio of 1.5:1 for 5 hours to obtain a mixed silicon source composed of Si and SiO2;
[0105] (4) 5 g of CaCO3 powder was placed at the bottom of the crucible to generate CO2 gas, and then the carbon source (3.67 g) and silicon source (7.5 g) obtained in step (2) and step (3) were placed in a corundum crucible. The crucible was covered with a lid and placed in a muffle furnace filled with argon for reaction. The argon flow rate was 10 ml / min, the maximum reaction temperature was 1500°C, the heating rate was 10°C / min, the holding time was 5 h, the cooling rate was 5°C / min, and 4.76 g of product was obtained after cooling to room temperature;
[0106] (5) The product obtained in step (4) was directly placed in a muffle furnace, heated to 900°C at a heating rate of 10°C / min, kept at this temperature for 2 hours, and cooled to obtain 2.13 g of SiO2@SiC (whose diameter distribution ranged from 53 to 88 nm).
[0107] (6) The product obtained in step (5) is subjected to a wave absorption performance test, and the optimal reflection loss (RL min ) is -16.44dB, the maximum effective absorption bandwidth (EAB max ) is 2.06GHz.
[0108] Comparative Example 1
[0109] The other conditions are the same as those in Example 1, except that calcium carbonate is not added in step (4); in step (5), the temperature is heated to 800°C at a heating rate of 10°C / min, kept at that temperature for 2 hours, and the product is cooled to obtain the optimal reflection loss (RL min ) is -10.25dB, the maximum effective absorption bandwidth (EABmax ) is 0.69GHz. The diameter distribution of the product is 115~236nm.
Claims
1. A method for preparing a cable-like structured SiO2@SiC composite absorbing material, characterized in that: The steps include: (1) Carbon source pretreatment: Grind the clean biomass into powder to obtain pretreated material; (2) Carbonization: The pretreated material obtained in step (1) is placed in a mold to be formed, and then placed in a furnace with a protective gas to be carbonized to obtain fluffy and porous biochar; (3) Silicon source pretreatment: Silicon powder and silicon dioxide are fully mixed by ball milling to obtain a mixed silicon source containing silicon and silicon dioxide; the mass ratio of silicon powder to silicon dioxide is 1-2:2-1; (4) High-temperature carbon thermal reduction: a layer of calcium carbonate powder is laid on the bottom of the crucible, and then the mixed silicon source obtained in step (3) is evenly spread on the surface of the CaCO3 powder, and then a corundum ring is placed as a support, and the fluffy porous biochar obtained in step (2) is placed on the upper end of the corundum ring; first, a protective gas is introduced, and then the temperature is raised to the reaction temperature, the reaction temperature is 1200-1600°C, and the reaction time is greater than 2 hours; (5) Carbon removal and controlled oxidation: The product obtained in step (4) is directly placed in a muffle furnace for heating to remove residual carbon and controllably oxidize to obtain SiO2@SiC nanowires; the temperature for carbon removal and controlled oxidation is 890-910°C and the time is greater than or equal to 100 min.
2. The method for preparing a cable-like structured SiO2@SiC composite absorbing material according to claim 1, characterized in that: The biomass is selected from at least one of coffee husks, peanut husks, rice husks, tobacco straws and cotton straws. After being ground into powder, the particle size thereof is 50-100 meshes.
3. The method for preparing a cable-like structured SiO2@SiC composite absorbing material according to claim 1, characterized in that: The powdered biomass is placed in a mold and formed by vacuum drying; the vacuum drying temperature is -50°C to -40°C, and the drying time is 12 to 24 hours.
4. The method for preparing a cable-like structured SiO2@SiC composite absorbing material according to claim 1, characterized in that: The pre-material obtained in step (1) is placed in a tubular furnace filled with argon gas for carbonization to obtain fluffy and porous biochar.
5. The method for preparing a cable-like structured SiO2@SiC composite absorbing material according to claim 4, characterized in that: During carbonization, the argon gas flow rate is 8-25 ml / min, the carbonization temperature is 500-800° C., and the time is greater than or equal to 100 min.
6. The method for preparing a cable-like structured SiO2@SiC composite absorbing material according to claim 1, characterized in that: In step (3), the purity of the silicon and silicon dioxide powder used is >99wt% and the mesh size is -100 mesh.
7. The method for preparing a cable-like structured SiO2@SiC composite absorbing material according to claim 1, characterized in that: In step (3), the silicon powder and silicon dioxide are mixed in a mass ratio of 1:
2.
8. The method for preparing a cable-like structured SiO2@SiC composite absorbing material according to claim 1, characterized in that: During high-temperature carbon thermal reduction, the flow rate of the protective gas outside the crucible needs to be controlled at 8-20 ml / min.
9. The method for preparing a cable-like structured SiO2@SiC composite absorbing material according to claim 1, characterized in that: In step (4), the reaction temperature is 1400-1600°C, more preferably 1580-1600°C; In step (4), after maintaining the reaction temperature, the temperature is lowered at a rate of 4-6°C / min; In step (4), the mass ratio of calcium carbonate to silicon source is 1:1.1 to 1.5, preferably 1:1.2 to 1.
5.
10. The method for preparing a cable-like structured SiO2@SiC composite absorbing material according to claim 1, characterized in that: The product obtained in step (4) is directly placed in a muffle furnace and heated to 890-910°C at a heating rate of 8-12°C / min, and then kept warm for 110-130 minutes to remove residual carbon and perform controllable oxidation to obtain SiO2@SiC nanowires.
Citation Information
Patent Citations
Method for preparing silicon carbide nano line
CN101386409A
Preparation method of biomass-based nano silicon dioxide with high specific surface area
CN112194146A
Silicon carbide fiber aerogel and preparation method thereof
CN113968582A
Lantern ring-shaped silicon carbide nanofiber aerogel material and preparation method thereof
CN115259161A
Manufacturing method of silicon carbide nanofibers from exfoliated graphite and amorphous silica
KR1020130102726A
